(untitled) (Eurasian Medical Research Periodical, 2025)
Carbon dioxide is an important pollutant that has recently led to deterioration of the environment. In particular, CO2 can be used not only as a greenhouse gas, but also as a source of carbon for the production of a number of high-quality products, such as light olefins. Lower olefins (C2H4 and c3h6) are the main petrochemical building blocks used to produce various chemicals.